REM Sleep Behavior Disorder Is Not Associated with a More Rapid Cognitive Decline in Mild Dementia - Chwiszczuk, Luiza; Breitve, Monica Haraldseid; Brønnick, Kolbjørn; Gjerstad, Michaela D.; Hynninen, Minna; Aarsland, Dag; Rongve, Arvid (Frontiers in Neurology, 2017)
Objectives: REM sleep behaviour disorder (RBD) is associated with cognitive dysfunctions and is a risk factor in the development of mild cognitive impairment (MCI) and dementia. However, it is unknown whether RBD is associated with accelerated cognitive decline in cases of established dementia. The main goal of this study was to determine whether patients with mild dementia with or without RBD differ in progression rate and in specific neuropsychological measures over a 4-year follow-up. Methods: This longitudinal prospective study, which is based on data from the DemVest study, compared neuropsychological measures in a mild dementia cohort. A diagnosis of probable RBD (pRBD) was made based on the Mayo Sleep Questionnaire (MSQ). Neuropsychological domains were assessed using the Mini Mental State Examination (MMSE), total score and figure copying, the California Verbal Learning Test-II (CVLT-II), Visual Object and Space Perception (VOSP) Cube and Silhouettes, the Boston Naming Test, the Stroop tests, Verbal Category Fluency and the Trail Making Test A and B. Results: Among 246 subjects, 47(19.1%) had pRBD at the baseline, and the pRBD group was younger and predominantly male. During a 4-year follow-up, we did not observe any significant differences in the rate of decline in neuropsychological measures. Patients with pRBD performed generally poorer in the visuo-constructional, visuo-perceptual and executive/attention tests in comparison with RBD-negative individuals. Conclusions: We found no significant differences in the progression rate of neurocognitive outcomes between dementia patients with and without RBD.